S.Vitte about the importance of railways in the formation and development of commercial seaworthiness - Petruchenko, O. A. (History of science and technology, 2017)
The article presents the process of relations between railways and sea ports. The analysis is based on the article by S.Vitte «Russian ports and railway tariffs». S.Vitte tried to find out how fair the criticism of the current tariff policy of the South-Western Railways was and to find out to what extent the interests of domestic ports could really be supported by railroad tariffs. First and foremost, Sergei Julievich emphasized that this issue should be fully addressed exclusively at the state level. He was convinced that a clear norm was needed that would establish general rules for all, without exception, railways, regardless of the form of ownership. After all, the railway cannot arbitrarily dispose of the movement of goods, it must work in accordance with social-economic laws.